Illuminating the decision-making strategies of anesthesia providers in challenging cases. (December 2020) - Biro, Joshua; Neyens, David M.; Jaruzel, Candace; Tobin, Catherine D.; Alfred, Myrtede; Coppola, Sarah; Abernathy, James H.; Catchpole, Ken R.
Medication errors and error-related scenarios in anesthesia remain an important area of research. Interventions and best practice recommendations in anesthesia are often based in the work-as-imagined healthcare system, remaining under-used due to a range of unforeseen complexities in healthcare work-as- done. In order to design adaptable anesthesia medication delivery systems, a better understanding of clinical cognition within the context of anesthesia work is needed. Fourteen interviews probing anesthesia providers' decision making were performed. The results revealed three overarching themes: (1) anesthesia providers find cases challenging when they have incomplete information, (2) decision-making begins with information seeking, and (3) attributes such as expertise, experience, and work environment influence anesthesia providers' information seeking and synthesis of tasks. These themes and the context within this data help create a more realistic view of work-as-done and generate insights into what potential medication error reducing interventions should look to avoid and what they could help facilitate.